The State papers domestic for the years 1656-1657 of the Interregnum - Cromwell, Oliver, 1599-1658 (Complete state papers domestic. 1625-1702. ;, 1656)
Admiralty Committee and Navy Commissioners' papers; Admiralty orders, bonds, accounts, etc.; Admiralty Committee warrants; letters and miscellaneous government papers, including Orders of the Council of State and petitions; Forest of Dean accounts; Customs and Excise accounts; and Navy bonds.